ANALYSIS OF TRANSFORMATIONAL LEADERSHIP IN THE IMPLEMENTATION OF EMPLOYEE DISCIPLINE IN BAPPELITBANGDA, WAJO DISTRICT - Asmanurhidayani,; Saniyyah Putri Salsabila Said,; Syamsiar,; Nurcaya, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
ANALYSIS OF TRANSFORMATIONAL LEADERSHIP IN THE IMPLEMENTATION OF EMPLOYEE DISCIPLINE IN BAPPELITBANGDA, WAJO DISTRICT